1998
DOI: 10.1006/cbir.1998.0304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interleukin‐6 on Proliferation and Proteoglycan Metabolism in Articular Chondrocyte Cultures

Abstract: Interleukin-6 (IL-6) levels are markedly increased in the synovial fluid of patients with rheumatoid arthritis or osteoarthritis. However, the effects of IL-6 on proliferation and proteoglycan metabolism in articular cartilage are not known. We demonstrated here the effects of human recombinant (hr) IL-6 on proliferation and proteoglycan metabolism in rabbit articular chondrocyte cultures. In vitro, these cells proliferated and produced abundant extracellular matrices. We found that 1-10 ng/ml of hrIL-6 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 0 publications
3
36
0
1
Order By: Relevance
“…Chondrocyte cloning is formed by cell proliferation and enhanced production of extracellular matrix without proper rearrangement of chondrocytes in the damaged cartilage (3), although the precise molecular mechanism is unknown. Growth factors including TGF␤ are suggested to play a role in chondrocyte cloning according to data from in vitro cloning assays (34,35). In the present study, we demonstrated that TGF␤-induced chondrocyte proliferation and chondrocyte cloning in agarose gel culture, which was stimulated by treatment with a mixture of TGF␤ and IGF-1, are abrogated by treatment with ADAM inhibitor, neutralizing anti-ADAM-12 antibody, or siRNA for ADAM-12.…”
Section: Discussionsupporting
confidence: 57%
“…Chondrocyte cloning is formed by cell proliferation and enhanced production of extracellular matrix without proper rearrangement of chondrocytes in the damaged cartilage (3), although the precise molecular mechanism is unknown. Growth factors including TGF␤ are suggested to play a role in chondrocyte cloning according to data from in vitro cloning assays (34,35). In the present study, we demonstrated that TGF␤-induced chondrocyte proliferation and chondrocyte cloning in agarose gel culture, which was stimulated by treatment with a mixture of TGF␤ and IGF-1, are abrogated by treatment with ADAM inhibitor, neutralizing anti-ADAM-12 antibody, or siRNA for ADAM-12.…”
Section: Discussionsupporting
confidence: 57%
“…Among these cytokines, IL-6 was detected in patients with OA as well as in patients with rheumatoid arthritis 22) . Pallotta et al 23) demonstrated that laser irradiation was effective in significantly reducing the total number of leukocytes as well as neutrophils in joint cavities.…”
Section: Discussionmentioning
confidence: 99%
“…Pallotta et al 23) demonstrated that laser irradiation was effective in significantly reducing the total number of leukocytes as well as neutrophils in joint cavities. Cartilage extracellular matrix degradation and suppression of extracellular matrix biosynthesis are regulated by a significant increase in the levels of cytokines in the affected synovial joint 22) . On the other hand, a critical function of IL-10 is to limit inflammatory responses 24) .…”
Section: Discussionmentioning
confidence: 99%
“…A significant elevation in the expression of IL-6 mRNA has been observed in OA-affected cartilage, and the IL-6 levels in serum and synovial fluid have been documented to be increased among OA patients (Kaneko et al, 2000). Moreover, human recombinant IL-6 has been demonstrated to enhance human recombinant IL-1β-induced proteoglycan degradation and to inhibit chondrocyte proliferation (Jikko et al, 1998). Known variations within the IL-6 gene have been repeatedly screened in a number of association studies.…”
Section: Discussionmentioning
confidence: 99%